2010
DOI: 10.1002/smi.1304
|View full text |Cite
|
Sign up to set email alerts
|

Sleep: an important factor in stress‐health models

Abstract: A growing body of literature supports the notion that psychological stress negatively impacts physical health. In parallel to this programme of stress/health investigations, researchers are demonstrating the deleterious health effects of poor sleep. The current study simultaneously examines the association of both stress and sleep with health. Two hundred and eighteen subjects completed an anonymous survey packet that included stress, sleep and health measures. Psychological stress (as assessed by both life-ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 75 publications
(74 reference statements)
3
75
0
Order By: Relevance
“…[4] Sleep is an important health factor in stress -health models. [39] Benham showed that the stress -health model used in his study was strengthened by adding sleep quality to it. Ekstedt et al [40] showed that patients suffering from occupational burnout also suffer from severe sleepiness and mental fatigue and that impaired sleep is an important factor in the development of burnout and fatigue.…”
Section: Introductionmentioning
confidence: 98%
“…[4] Sleep is an important health factor in stress -health models. [39] Benham showed that the stress -health model used in his study was strengthened by adding sleep quality to it. Ekstedt et al [40] showed that patients suffering from occupational burnout also suffer from severe sleepiness and mental fatigue and that impaired sleep is an important factor in the development of burnout and fatigue.…”
Section: Introductionmentioning
confidence: 98%
“…Insomnia is assumed to play a crucial role in the complex relationship between stress and health [10]. By undermining regulatory systems and immune functions in its wake, chronic insomnia can aggravate other acute and chronic diseases, which, in turn, may impair sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…To date, research examining the effects of relationship quality or stress exposure on sleep outcomes has relied on either cross‐sectional data (e.g., Benham, ; Drake et al, ) or data regarding daily variations in relationship quality or stress on sleep over brief periods of time (e.g., Kane et al, ; Selcuk et al, ). Although this important work has demonstrated the significance of concurrent interpersonal processes and stressors for sleep quality and duration, the extent to which relationship functioning and stress exposure exert cumulative impacts on sleep over time remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to laboratory stressors prior to sleep, such as engaging in a stressful task (Chen, Jarrin, Ivers, & Morin, ) or anticipating giving a speech (Germain, Buysse, Ombao, Kupfer, & Hall, ), predicts lower sleep efficiency, delayed sleep onset, and more frequent nighttime awakenings. Cross‐sectional studies have also confirmed that exposure to more stressful everyday hassles (Benham, ) and stressful life events (Drake, Pillai, & Roth, ) are associated with sleep impairments (e.g., worse subjective sleep quality, higher risk for insomnia).…”
Section: Introductionmentioning
confidence: 90%